Analysis of Weight, Composition, Density, and Recycling Potential of Floating Marine Debris in Pasie Nan Tigo Area, Padang City - Rizki Aziz; Budhi Primasari; Cici Amelia Edriani (Universitas Diponegoro, 2023)
Floating marine debris is a solid materials that is produced and disposed of in the marine environment. This study aimed to analyze the weight, composition, density, and recycling of potential marine debris. The samples were taken at three locations on rainy and non-rainy days. Location was selected based on trawl activities, estuary, and public activities. The method of sampling was using trawl. The weight on rainy days was 1.2 to 2.2 g/m2, while on non-rainy days was 1.6 to 2.7 g/m2. Total weight 689.2 kg non rainy conditions and on rainy conditions 895.4 kg. There were four types of waste obtained, which were plastic, wood, fiber, and rubber. The highest percentage in the composition was plastic, which was 48 to 61%. The density of waste on non-rainy days was 0.1 -1.3 g/m2 and on rainy days conditions range 0.2 - 1.7 g/m2. The highest density of waste was plastic of 1.6 g/m2. The recycling potential of plastic, wood, and fabric was 100% respectively. The recycling potential of plastic, wood, and fabric was 100% respectively. The recommendation for floating marine debris is 3R + 1P (recycling, reuse, recovery, and participant).